Maritime logistics : a complete guide to effective shipping and port management - Song, Dong-Wook (Kogan Page, 2012)
"Current globalisation and borderless operations in manufacturing and services industries are creating a greater demand for international transport and logistics. Maritime (shipping and ports) is one of the key components in this business pattern. It is now estimated that approximately 90% of global trading freights are moved by maritime mode.